Factors Influencing Behavioral Intention To Use Telemedicine Services: Modified-Utaut3 Model - Febrianti, Andi Achelya (UNIVERSITAS PAKUAN, 2022)
Covid-19 has prompted digitalization in many aspects of people’s lives. Digitalization not only disrupts human interaction but also many forms of services, including health. Digitalization in the health sector has been developing telemedicine – a digital system that provides many forms of services such as consultation with medical professionals from afar. Telemedicine services have been growing in Indonesia these late years, although Indonesia still deals with an inadequate healthcare system. Therefore, this study examines factors influencing behavioral intention to use telemedicine services on Indonesians by using a modified UTAUT-3 model. A total of 350 participants answered the questionnaire form. The result of the PLS-SEM method reveals that social influence, facilitating conditions, and habit have the strongest influences on intention to use telemedicine services. The study also found that gender has no moderating effect. The research implication would be beneficial for the policymakers, researchers, as well as telemedicine industry in implementing and promoting telemedicine usage, especially in the developing countries.